2015
DOI: 10.1177/1073191115607973
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the Cattell–Horn–Carroll Theory of Cognitive Abilities in the Factor Structure of the Dutch-Language Version of the WAIS-IV

Abstract: The Cattell-Horn-Carroll (CHC) theory of cognitive abilities has been guiding in the revision of the Wechsler Adult Intelligence Scale-Fourth edition (WAIS-IV). Especially the measurement of fluid reasoning (Gf) is improved. A total of five CHC abilities are included in the WAIS-IV subtests. Using confirmatory factor analysis, a five-factor model based on these CHC abilities is evaluated and compared with the four index scores in the Dutch-language version of the WAIS-IV. Both models demonstrate moderate fit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Meta analysis of case-control studies of patients with ADHD, for example, display significant weaknesses in several key EF domains like response inhibition, vigilance and planning (Willcutt et al, 2005 ). As Wechsler batteries primarily tap into crystallized intelligence and do not specifically measure attention and EF (van Aken et al, 2014 , 2017 ), future studies on KBG syndrome could focus on more specific aspects of neurocognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Meta analysis of case-control studies of patients with ADHD, for example, display significant weaknesses in several key EF domains like response inhibition, vigilance and planning (Willcutt et al, 2005 ). As Wechsler batteries primarily tap into crystallized intelligence and do not specifically measure attention and EF (van Aken et al, 2014 , 2017 ), future studies on KBG syndrome could focus on more specific aspects of neurocognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have tried to unify intelligence and neuropsychological assessment based on the CHC model [58,[63][64][65][66][67][68][69][70][71]. For example, Jewsbury et al [65] showed that popular neuropsychological EF tests were subsumable under CHC broad cognitive abilities based on factor analytic methods, although particular EF tests were related to distinct CHC constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the few exceptions to that rule were discussed above in detail. These studies had their methodological grounding in factor analytic methods [64,65,[68][69][70], in regression methods [71], or in neuropsychological patient studies [15,72].…”
Section: Introductionmentioning
confidence: 99%
“…As for the WAIS-IV, the original index scores (VCI, PRI [Perceptual Reasoning Index], WMI, and PSI) were translated to CHC scores (Gc, Gv, Gf, Gsm, and Gs), according to the CHC factors found in previous research (Benson et al, 2010;Van Aken et al, 2017 Figure Weights, and Arithmetic. Gsm consists of the WMI subtests Digit Span and Letter-Number Sequencing, and Gs is made up of PSI subtests Symbol Search, Coding, and Cancellation.…”
Section: Wais-iv (N = 194)mentioning
confidence: 99%
“…Previously, we also studied latent constructs of EF and intelligence test through factor analysis, finding overlap mainly between EF and Gf/Gv (Van Aken et al, 2014;Van Aken et al, 2016;Van Aken et al, 2017). As Schneider and McGrew (2012) state, other (multivariate) statistical techniques should be used next to factor-analytic investigations of latent constructs, "to allow for the simultaneous examination of content (facets), processes, and processing complexity of CHC measures" (p. 109).…”
mentioning
confidence: 99%